Discovering dependencies between domains of redox potential and plant defence through triplet extraction and copulas. (2018) - Miljkovic, Dragana; Lavrač, Nada; Bohanec, Marko; Boshkoska, Biljana Mileva
Knowledge discovery, especially in the field of literature mining, is often involved in searching for some interconnecting concepts between two different literature domains, which might bring new understanding of both domains. This paper presents a new approach to discovering dependencies between different biological domains based on copula analysis of literature mining results. More specifically, we have explored dependencies between literature from the domains of plant defence response and redox potential. Copula analysis of triplets, which are extracted by Bio3graph tool, shows that dependencies exist between these two domains indicating a potential for cross-domain literature exploration. Bio3graph is a rule-based natural language processing tool which extracts relations in the form (subject, predicate, object) triplets. It is publicly available at http://ropot.ijs.si/bio3graph/software/. Copula analysis was performed by using Clayton and Frank fully nested copulas and the software is publicly available at: http://source.ijs.si/bmileva/copulasfordexapps.git.